2 Role of cardiac magnetic resonance (CMR) in the identification of arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) phenocopies. (26th April 2015) - Amadu, AM; Baritussio, A; Dastidar, A Ghosh; Rodrigues, J; Hamilton, M; Manghat, N; Bucciarelli-Ducci, C
Abstract : Introduction: ARVC/D is an autosomal dominant genetic heart disease. As part of the diagnostic tools included in the 2010 diagnostic Task Force Criteria, patients are often referred to CMR to rule out the diagnosis. However, the diagnosis is often challenging due to pathologies mimicking ARVC/D. Aim: To assess the prevalence of ARVC/D phenocopies in patients referred to CMR for suspected ARVC/D. Methods: We retrospectively analysed the registry data of patients with suspected ARVC/D referred to CMR in a large UK tertiary centre from January to December 2014. We identified 125 patients (56% male, median age 40 years) with suspected ARVC/D on the basis of symptoms and clinical presentation, family history of ARVC/D or sudden cardiac death, abnormal electrocardiogram or transthoracic echocardiography. A comprehensive CMR protocol (including cine and late gadolinium enhancement sequences) was performed in all patients. Results: ARVC/D phenocopies were identified in 12 patients (9.6%): 5 patients had ischaemic heart disease and 7 had non-ischaemic heart disease (Table 1 ). In the latter group, congenital absence of pericardium (Figure 1 ), idiopathic dilated cardiomyopathy, left ventricular non compaction, arrhythmogenic left ventricular cardiomyopathy (ARVC/D variant), anomalous venous return, atrial septal defect with left to right shunting, and asymmetric pectus excavatum distorting right ventricular (RV) morphology were identified. Conclusions: CMR shows a remarkable role, both in diagnosing ARVC/D and ruling out its mimics. Correct diagnosis of the underlying pathology in patients with suspected ARVC/D is fundamental, given the non-negligible prevalence of phenocopies (9.6% in our population) and its subsequent impact on clinical management.